Cluster and Grid Computing: A Detailed Comparison - Ahuja, A (International Journal of Computer Sciences and Engineering, 2025)
Computing power has gained momentum in the last few years with the incorporation of cluster and grid computing models. With supercomputers, some issues need to be tackled in terms of solving the intensive computational problem tasks in an economical way. Even high performance computing but with low cost was not possible earlier with supercomputers but with the advent of cluster and grid computing technologies it is no more restricted to the multi-institutional virtual organizations but becomes a reality for the small scale organizations also. This paper discusses the cluster and grid computing technologies, and gives an insight details in terms of vital features of clusters and grids, challenges, applications, tools and simulation environment for their implementation and comparative analysis of the same.